50. Neurophysiological assessment of small midlateral medullary syndromes. Issue 1 (January 2015) - Alibardi, A.; Gorini, M.; Leone, C.; Pierelli, F.; Currà, A.
<x xml:space="preserve">Abstract</x> To define the extent of damage caused by an ischemic lesion of the left midlateral upper medulla in a 75 year-old patient we performed extensive neurophysiological assessment including somatosensory- and laser-evoked potentials from the upper limbs, exteroceptive and nociceptive blink reflex (tested using a concentric planar electrode), masseter inhibitory reflex and trigeminal laser-evoked potentials. Cutaneous laser stimulation of the right hand failed to evoke any cortical response; somatosensory evoked potentials, exteroceptive and nociceptive blink reflex, masseter inhibitory reflex, and trigeminal laser-evoked potentials were normal on both sides. Neurophysiological data proved the involvement of the left spinothalamic tract and the sparing of the trigeminal descending nucleus, ventral secondary ascending trigeminal pathways, and dorsal column-medial lemniscus sensory pathway. Neurophysiological findings, along with clinical and instrumental evidence of ipsilateral palatolaryngeal palsy indicating damage of the nucleus ambiguous, allow the diagnosis of Avellis' syndrome, a rare brainstem syndrome originally described in 1891. Routine use of neurophysiological techniques provides precise identification of the neural structures involved in small medullary syndromes, thus refining diagnosis and favouring a precise identification of the vascular territory involved.